2018
DOI: 10.18203/2394-6040.ijcmph20181226
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitudes and practices toward prevention of hepatitis B virus infection among medical students in Geetanjali Medical College, Udaipur

Abstract: Background: Hepatitis B virus (HBV) infection is one of the major public health problems in the world. According to the recent estimates, about one-third of the world population is infected with HBV. Health care workers (HCWs) are at high risk of HBV infection in the health care settings. The prevalence rate of HBV in HCWs is about 2–10 times higher than the general populations in the world.Methods: A cross sectional study was conducted at GMCH, Udaipur from March 2017 to August 2017 on a pretested, precoded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…Besides, the levels of attitudes were reported favorable but the levels of good practices were illustrated with low frequency as those concluded in the present study. 15,26 Likewise, the results of another study conducted among Ethiopian medical students indicated that the levels of knowledge among 80% of the participants was good which were in agreement with findings of the present study although, in this report, the favorable levels of attitudes were reported about 10% higher than that in the present study. 6 The findings of another survey in 2017, as one of the comprehensive studies on the measurement of the levels of KAP concerning viral hepatitis around the world on 2500 Iranian medical students also demonstrated that the participants' score for the construct of levels of knowledge was 7.35 (out of 10), that was 4.88 for the parameter of levels of attitudes (from -20 to +20), and such a value was 5.67 (out of 9) for the construct of levels of practices which illustrated a bad status, especially in the parameters of levels of attitudes and practices.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Besides, the levels of attitudes were reported favorable but the levels of good practices were illustrated with low frequency as those concluded in the present study. 15,26 Likewise, the results of another study conducted among Ethiopian medical students indicated that the levels of knowledge among 80% of the participants was good which were in agreement with findings of the present study although, in this report, the favorable levels of attitudes were reported about 10% higher than that in the present study. 6 The findings of another survey in 2017, as one of the comprehensive studies on the measurement of the levels of KAP concerning viral hepatitis around the world on 2500 Iranian medical students also demonstrated that the participants' score for the construct of levels of knowledge was 7.35 (out of 10), that was 4.88 for the parameter of levels of attitudes (from -20 to +20), and such a value was 5.67 (out of 9) for the construct of levels of practices which illustrated a bad status, especially in the parameters of levels of attitudes and practices.…”
Section: Discussionsupporting
confidence: 91%
“…It was also possible that different countries would implement specific intervention and prevention programs and plans based on the priorities of their health systems, so variations in the levels of KAP could be attributed to this factor. 15,26,27 In addition, the difference in study time, especially comparing Iranian investigations with one another, could be assumed as one other reason for the differences between the findings. 12,20,22 However, in the overall conclusion, it seemed that the frequency of good levels of knowledge among HCWs and medical students in the majority of the studies conducted in developing countries was about 80% which seemed to be desirable despite being mathematically distant from the ideal status of 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that despite increasing prevalence of HBV, there is paucity of knowledge, attitude and practice (KAP) on Hepatitis B infection and its prevention among medical students. [8][9][10][11] Objective of the study was to assess the knowledge, attitude and practices on prevention of hepatitis B infection among medical students of Sree Mookambika Institute of Medical Sciences, Kulasekharam, Tamil Nadu.…”
mentioning
confidence: 99%